State Fundamental Consensus in Indonesia's Foreign Policy Implementation Amid Contemporary Global Geopolitical Dynamics: A Normative-Strategic Analysis - Heriyana; Nabila Saifani Azzahra (Journal of World Science, 2026)
This research conducts an in-depth examination of the relationship between Indonesia's four fundamental state consensuses Pancasila, the 1945 Constitution (UUD 1945), Bhinneka Tunggal Ika, and the Unitary State of the Republic of Indonesia (NKRI) within the Wawasan Nusantara framework in the implementation of an independent-active foreign policy amidst increasingly complex and multipolar global geopolitical dynamics. This research employed a normative-strategic analytical approach integrated with Kenneth Waltz's Domestic Level of Analysis and middle power diplomacy conceptualization. Using literature study, the research finds that Pancasila as the ideological foundation functions as an ideological filter providing humanistic value orientation alongside a normative conflict resolution mechanism in diplomatic decision-making. Furthermore, the 1945 Constitution affirms the constitutional mandate of the independent-active principle, which in the multipolar era must be operationalized as strategic autonomy, namely Indonesia's capacity to maintain strategic maneuverability between major powers. Additionally, Bhinneka Tunggal Ika promotes an inclusive diplomatic approach that positions Indonesia as a unique bridging actor between the Islamic world, Asian democracy, and the global community. Finally, NKRI through Wawasan Nusantara shapes a maritime geopolitical identity that forms the basis for Indonesia's legitimate interest claims in the Indo-Pacific region. This study identifies five critical geopolitical arenas the South China Sea dispute, Indo-Pacific rivalry, Middle East conflict, Myanmar crisis, and post-COVID-19 global governance and analyzes how fundamental state consensuses provide normative guidance across each. The original contribution lies in developing the Pancasila-Geopolitics Framework (PGF), a new analytical model that systematically connects domestic ideological foundations with Indonesia's foreign policy behavior.